An Error Analysis of Students’ Translation from Indonesian into English Text at the 6th Semester Students of English Education Study Program in UIN Sjech M. Djamil Djambek Bukittingi - Hartati, Zuli; Kardena, Absharini; Sakti, Genta; Putri, Hilma Pami (Lembaga Yasin AlSys, 2023)
This research was due to some problems that were found in the 6th semester students of English Education Study Program in UIN Bukittingi. First, the students had vocabulary problem in translating Indonesian to English, especially the ability to use the proper vocabulary in translating. Second, the students had grammar problem in translating Indonesian to English, especially tenses and time condition. The purpose of this research was to find out the type of error that they make when translating text from Indonesian into English and to find out the most frequent error the students make when translating text from Indonesian into English. This research was a descriptive quantitative research. The sampling technique that researcher uses was total sampling. The instrument that was used in a research was translation test. It was a text consists of three paragraphs in Indonesian that must be translated into English. The researcher found that addition errors were made 7.31% of the time, omission errors were made 27.74% of the time, literalness errors were made 13.98% of the time, ambiguity errors were made 17.42% of the time, punctuation errors were made 4.95% of the time, spelling errors were made 3.44% of the time, and capitalization errors were made 25.16% of the time. It can be concluded that omission error is the most frequent error, followed by capitalization, ambiguity, literalness, addition, punctuation, and spelling. This make spelling as the least frequent error that the students made.